The mothers in me. Issue 1 (February 2019) - Katila, Saija
Abstraction of the narrative The paper aims to evoke readers' reflective and affective capacities and thereby facilitate understanding of the multisensorial, affective, and relational nature of knowing and becoming. It highlights the role of embodied knowing in becoming by following the journey of an individual faced with sudden trauma. It describes the affective energies crossing time and space in the continuously changing sociomaterial networks of relationships encountered in different organizational settings, be they in academia, health and social services, family, or otherwise. The paper is based on an auto-ethnographic narrative of becoming a mother that connects individual experiences with cultural understandings. The narrative is an outcome of a diffractive analysis of becoming; knowing emerges during the course of a writing process in which theoretical understandings, emotions, concepts, discourses, embodied experiences, and affects come together. The paper brings out the multiplicity of contradictory discourses involved in knowing and becoming. In so doing, it highlights the entangled coexistence of body and mind, reality and imagination, public and private, reason and emotion, as well as past, present, and future.